Cultural intelligence as a determinant of performance: Unveiling the role of job satisfaction and the impact of knowledge sharing - Yusuf, Luthfi; Rostiana, Rostiana; Budiana, I Made (Institut Agama Islam Negeri Langsa, 2024)
The phenomenon of cultural diversity in the workplace increasingly influences the dynamics of employee performance and interactions. This study aims to deepen the understanding of the impact of cultural intelligence and knowledge sharing on employee performance, with job satisfaction serving as a mediator. Employee performance is defined as the ability and outcomes achieved by employees in fulfilling their tasks. This research employs a quantitative approach, utilizing four questionnaires based on a 1-5 Likert scale to measure cultural intelligence, knowledge sharing, performance, and job satisfaction. The sample consists of 116 employees from X Company, a coal-fired power plant located in Cirebon, West Java, selected based on specific criteria. The results of the analysis indicate that job satisfaction mediates the relationship between cultural intelligence and performance, but does not mediate the relationship between knowledge sharing and performance. This study provides implications for multicultural organizations to focus on the development of cultural intelligence to enhance employee satisfaction and performance.